2022
DOI: 10.18280/ijsdp.170524
|View full text |Cite
|
Sign up to set email alerts
|

Looking into Corporate Boardrooms Through the Lens of Gender Diversity: A Bibliometric Review and META Analysis

Abstract: The present study examines the literature on the corporate boardroom through the lens of gender diversity. The study identified 1413 studies from Scopus database to identify the corporate board gender diversity ranging from a period of 1998 to 2021 (November). The identified studies are reviewed by using VOS viewer software and R-Studio. The study also employed META analysis to further analyse the data and draw meaningful results. The study identifies the current themes in the literature of corporate boardroom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Despite the limitations of this study, significant due diligence has been performed to ensure that the quantitative measure the researcher seeks to introduce is yet to be developed. Moreover, despite the limitations of bibliometric analysis, it is a highly suitable method for achieving the research objectives due to its ability to tabulate and visualize the data which can provide great insight on the literature reviewed [27].…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…Despite the limitations of this study, significant due diligence has been performed to ensure that the quantitative measure the researcher seeks to introduce is yet to be developed. Moreover, despite the limitations of bibliometric analysis, it is a highly suitable method for achieving the research objectives due to its ability to tabulate and visualize the data which can provide great insight on the literature reviewed [27].…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…The study also used VOS viewer application to graphically demonstrate the data in network form. VOS viewer presents the network to analyze the co-citation, co-occurrence, bibliographic coupling to find out the research theme in the financial development and carbon emission domain (Basher et al, 2022;Rabbani et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The McKinsey & Company study from 2015, which identified a link between gender-diverse boards and http://jier.org better financial performance, is one of the most notable conclusions. According to Basher et al (2022), businesses with the greatest amount of gender diversity were 15% more likely to have financial gains that were higher than the industry average. A 2016 Credit Suisse analysis that demonstrated that organizations with more women on their boards saw superior share price performance corroborated this association.…”
Section: Organizational Performancementioning
confidence: 99%